A REVIEW ON EMOTIONAL INTELLIGENCE PERCEPTION AMONG EDUCATORS IN POLYTECHNIC - Muniamal (International Journal of Advanced Science and Technology, 2020)
The understanding of Emotional Intelligence is vital in upgrading the quality of educationprofessional development. It is a quality that enables us to confront our emotions, identify othersemotions and build good social relationship with others. Educators are role models for students tolearn emotionally intelligent behavior and the awareness of emotional intelligence among educatorswould enable them to enhance personal and professional competence. This study is an attempt toevaluate the insight of emotional intelligence among educators in a Polytechnic. A qualitativeapproach, with open ended questions and a focus group method was applied. Research conductedimplied that there is a need to coach educators onemotionalintelligenceinordertoproducestudentswhoareabletoperformuniversally in future.